2021
DOI: 10.1111/all.14800
|View full text |Cite
|
Sign up to set email alerts
|

Single‐dose prolonged drug provocation test, without previous skin testing, is safe for diagnosing children with mild non‐immediate reactions to beta‐lactams

Abstract: Introduction: Mild non-immediate reactions (NIRs) to beta-lactams (BLs) are the most frequent manifestation of drug allergy in children. The diagnostic approach is complex as the utility of skin tests (STs) and lymphocyte transformation tests (LTTs) is controversial. Drug provocation test (DPT) is the gold standard, although no standardized protocols exist. We aimed to investigate the utility of DPT in a unique dose without previous STs, and LTTs in the diagnosis of NIRs to BLs in children. Methods:We prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 80 publications
0
45
0
Order By: Relevance
“…Given the unreliability of self‐reported clinical history and the poor predictive value of skin tests, direct DPT procedures by skipping skin tests in appropriate patients are gaining acceptance as a safe and accurate delabeling strategy 2,35,36,41,42,49,50 . In fact, an increasing number of pediatric studies have challenged the guidelines by performing direct DPT without prior skin testing in mild NIRs to BLs 33,36,42,49,51,52 . In these studies, only 3.4%–14% of children with a history of mild NIR had a positive DPT and only mild reactions were reported after DPT, supporting the safety of this procedure in children.…”
Section: Alternative Approaches Mainly Targeting To Delabel Bl Allergymentioning
confidence: 97%
“…Given the unreliability of self‐reported clinical history and the poor predictive value of skin tests, direct DPT procedures by skipping skin tests in appropriate patients are gaining acceptance as a safe and accurate delabeling strategy 2,35,36,41,42,49,50 . In fact, an increasing number of pediatric studies have challenged the guidelines by performing direct DPT without prior skin testing in mild NIRs to BLs 33,36,42,49,51,52 . In these studies, only 3.4%–14% of children with a history of mild NIR had a positive DPT and only mild reactions were reported after DPT, supporting the safety of this procedure in children.…”
Section: Alternative Approaches Mainly Targeting To Delabel Bl Allergymentioning
confidence: 97%
“…So far, in NIR to βLs, it seems to be safe to administer the first dose of antibiotic in a single dose. 20,24,[32][33][34] In our study, we fractionated the dose as recommended by the EAACI position paper. 5 As reported above, only one patient reacted 30 min after the first fractionated dose (1/10) with mild urticaria.…”
Section: Re Sultsmentioning
confidence: 99%
“…In addition, a prolonged DPT results in increased confidence in the future use of the same drug when compared with a single‐day DPT. On the other hand, a prolonged DPT is questioned because of its impact on the gut microbiota and the potential risk of increasing antibiotic resistance 1,3,8–24 . So far there is no agreement on the best protocol to be used that reaches the best compromise between safety, time consumption, and potential side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 These results have recently been confirmed in an European population of children. 10 Aside from the inconvenience and potential need for specialty assessment, for very low-risk patients, the use of skin testing would be expected to perform poorly considering their low pre-test probability of a reaction. Several other studies have demonstrated that a single or two-step direct ingestion challenge with penicillins such as amoxicillin is a safe and practical strategy to remove a label of penicillin allergy.…”
Section: E D I T O R I a L Addressing Beta-lactam Allergy: A Time For...mentioning
confidence: 99%